Radiation damage to macromolecules: kill or cure? - Garman, Elspeth F.; Weik, Martin (Journal of synchrotron radiation, 2015)
Radiation damage induced by X‐ray beams during macromolecular diffraction experiments remains an issue of concern in structural biology. While advances in our understanding of this phenomenon, driven in part by a series of workshops in this area, undoubtedly have been and are still being made, there are still questions to be answered. Eight papers in this volume give a flavour of ongoing investigations, addressing various issues. These range over: a proposed new metric derived from atomic B‐factors for identifying potentially damaged amino acid residues, a study of the relative damage susceptibility of protein and DNA in a DNA/protein complex, a report of an indication of specific radiation damage to a protein determined from data collected using an X‐ray free‐electron laser (FEL), an account of the challenges in FEL raw diffraction data analysis, an exploration of the possibilities of using radiation damage induced phasing to solve structures using FELs, simulations of radiation damage as a function of FEL temporal pulse profiles, results on the influence of radiation damage during scanning X‐ray diffraction measurements and, lastly, consideration of strategies for minimizing radiation damage during SAXS experiments. In this short introduction, these contributions are briefly placed in the context of other current work on radiation damage in the field.